Transversal Rationality: The Challenge of Assigning ‘Cognitive Parity’ to the Sciences and Theology - Watson, Simon (Toronto journal of theology, 2011)
J. Wentzel van Huyssteen uses Calvin Schrag's notion of transversal rationality to argue for a "cognitive parity" between the sciences and religion, implying a degree of separation and equality that can be problematized. Drawing on Lawrence Blum's criticism of Charles Taylor's "The Politics of Recognition," this essay argues that culture and its diverse products, like science and religion, cannot be treated as abstract totalities to which a value can be determined and affixed. Instead, we could focus on what distinctive values are realized by the cultural form in its own right, rather than compelling a comparison using a language of equivalency. This shift in focus from "equal respect" to "cultural respect" does not mean that one cultural form is superior to the other, only that the framework of equivalency be jettisoned. Science and theology operate in different but shared dimensions, such that science might better be understood as a tool within the larger theological enterprise. The problem, then, is not the universalism of science but the exclusivity of scientism. Science should be understood then as a source within theology, in the same manner as human experience, tradition, and Scripture, and approached using rational judgment, in dialogue and discernment within a believing community.